#TITLE_ALTERNATIVE# - (NIM 20205004), ERNI
Mineral magnetics of Lumpur Sidoarjo (LUSI) have been identified using rock magnetic method. LUSI samples were obtained directly from the main hole of eruption in Siring, Porong, Sidoarjo. By identifying the types and the concentration of magnetic minerals in LUSI, we expect to contribute additional information on the source and mechanism of LUSI. The investigation was based on the measurement of magnetic susceptibility, (anhysteritic remanent magnetization), and IRM (isothermal remanent magnetization). Magnetic susceptibility measurements show that concentration of magnetic minerals in LUSI is very small (<0.01%), while analyses of IRM saturation show that the predominant magnetic mineral in LUSI is magnetite. Moreover, from low field and ARM susceptibilities, we observe that grain size of magnetic minerals vary from 5 to 20 μm. The concentration of magnetite suggest that the source of LUSI is sediments in reductive environment, where dissolution and diagenesis occur during oxic and anoxic transition. The most likely source of LUSI is the thick bluish gray caly of Kalibeng Formation.